Sagittal Plane Kinematic Deviations and Spatio-Temporal Gait Characteristics in Children with Idiopathic Toe Walking: A Comparative Analysis Using Statistical Parametric Mapping - Rocio Pozuelo-Calvo; Almudena Serrano-Garcia; Yolanda Archilla-Bonilla; Angel Ruiz-Zafra; Manuel Noguera-Garcia; Kawtar Benghazi-Akhlaki; Miguel Membrilla-Mesa; Carla DiCaudo; Jose Heredia-Jimenez (Diagnostics, 2025)
Background/Objectives: Idiopathic Toe Walking (ITW) is a pediatric gait disorder characterized by persistent toe-to-heel ambulation in the absence of neurological, orthopedic, or developmental abnormalities. While spatio-temporal parameters often remain within normal ranges, subtle but clinically significant kinematic deviations may underlie compensatory mechanisms that sustain gait functionality. This study aims to evaluate spatio-temporal and sagittal plane kinematic differences between children with ITW and typically developing peers using Statistical Parametric Mapping (SPM). Methods: A cohort of 30 children with ITW and 30 typically developing peers aged 6–12 years participated in this study. Spatio-temporal variables, including step length, cadence, stride length, walking speed, single support phase, and swing phase, were analyzed using a three-dimensional motion capture system. Sagittal plane kinematics of the pelvis, hip, knee, and ankle were compared between groups using SPM to identify significant deviations across the gait cycle. Results: Significant differences were identified in the single support and swing phases, with higher values observed in the ITW group (p < 0.05). Sagittal plane kinematics revealed a consistent reduction in anterior pelvic tilt (p = 0.002), reduced hip and knee flexion during stance and swing phases (p < 0.001), and excessive ankle plantarflexion during early stance and terminal swing phases (p < 0.001). The plantarflexion observed at the end of the gait cycle corresponded to early gait phases due to methodological considerations of the coordinate-based event detection algorithm. Conclusions: Children with ITW demonstrate distinct spatio-temporal adaptations, including increased single support and swing phases, along with reduced walking velocity compared to typically developing peers. These findings, coupled with significant sagittal plane kinematic deviations, suggest altered neuromuscular control and joint mechanics. These insights highlight the importance of detailed kinematic analyses to identify biomechanical deficits and inform targeted interventions. Future research should explore the long-term musculoskeletal consequences of these deviations and optimize therapeutic strategies, such as physical therapy and orthotic interventions, to improve gait functionality and quality of life.